2021
DOI: 10.1186/s41232-021-00164-9
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation, functions, and roles of T follicular regulatory cells in autoimmune diseases

Abstract: T follicular helper cells participate in stimulating germinal center (GC) formation and supporting B cell differentiation and autoantibody production. However, T follicular regulatory (Tfr) cells suppress B cell activation. Since changes in the number and functions of Tfr cells lead to dysregulated GC reaction and autoantibody response, targeting Tfr cells may benefit the treatment of autoimmune diseases. Differentiation of Tfr cells is a multistage and multifactorial process with various positive and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 95 publications
(116 reference statements)
0
14
0
Order By: Relevance
“…4 A to C, and Supplementary Data 12 ) 36 38 . These follicular-like regulatory CD4 + T cell subsets have been postulated as critical regulators of adaptive responses in lymphoid organs 39 41 , but so far have not been reported in the brain during infections. These populations seemed dynamic over the course of infection, with chronic stages associated with a 1.27- and 1.61-fold increase in the abundance of Cd4 + T cells compared to other subclusters (23.64%, 30.21%, and 38.1% in naïve, 25dpi, and 45dpi, respectively) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4 A to C, and Supplementary Data 12 ) 36 38 . These follicular-like regulatory CD4 + T cell subsets have been postulated as critical regulators of adaptive responses in lymphoid organs 39 41 , but so far have not been reported in the brain during infections. These populations seemed dynamic over the course of infection, with chronic stages associated with a 1.27- and 1.61-fold increase in the abundance of Cd4 + T cells compared to other subclusters (23.64%, 30.21%, and 38.1% in naïve, 25dpi, and 45dpi, respectively) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, ICOS stimulation induces RORC2 and c-Maf expression in Th17 cells and Bcl-6 expression in TFH cells, leading to increased secretion of IL-17 and IL-21, respectively [ 56 , 61 ]. What is more, ICOS ligation upregulates transcription factors FOXP3 and Bcl-6 and promotes IL-10 and TGF- β production in TFR cells [ 62 ] ( Figure 2 ).…”
Section: Inducible Costimulator (Icos)mentioning
confidence: 99%
“…Notably, these regulatory Cd4 + T cells also express high levels of marker genes typically associated with follicular helper T cells such as Maf and Slamf5 ( Figure 4A to 4C, and S2I Table ) (Bauquet et al, 2009; Cannons et al, 2010; Nurieva and Chung, 2010). These follicular-like regulatory CD4 + T cell subsets have been postulated as critical regulators of adaptive responses in lymphoid organs (Hao et al, 2021a; Miles and Connick, 2018; Vaeth et al, 2019, 2019; Wollenberg et al, 2011), but so far have not been reported in the brain during infections. These populations seemed dynamic over the course of infection, with chronic stages associated with a two-fold increase in the abundance of Cd4 + T cells compared to other subclusters (8.2%, 19.3%, and 20.85% in naïve, 25dpi, and 45dpi, respectively) ( Figure 4B and 4D ), consistent with previous reports (Laperchia et al, 2016; Lyck et al, 2003).…”
Section: Resultsmentioning
confidence: 99%